2018
DOI: 10.1186/s40545-018-0148-8
|View full text |Cite
|
Sign up to set email alerts
|

Country ownership and sustainability of Nigeria’s HIV/AIDS Supply Chain System: qualitative perceptions of progress, challenges and prospects

Abstract: BackgroundThe emergency response phase to HIV epidemic in Nigeria and other countries saw to the deployment of donors’ resources with little consideration for country ownership (CO) and sustainability. The progress that has been made in the fight against the pandemic has however precipitated a paradigm shift towards CO and sustainability. With the decline in donors’ funding, countries must continually evaluate their readiness to own and sustain their HIV response especially the supply chain system (SCS) and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…Furthermore, while prior HIV treatment interventions, in particular, have adopted a 1:10 ratio of navigator-peers [ 57 ], this was perceived as unsustainable for a volunteer force. These findings are consistent with concerns among stakeholders across SSA [ 58 ], and in Nigeria more specifically [ 59 ], about efficiencies in systems of HIV care given reduced funding from external donors, which have impacted the quantity [ 60 ] and quality of HIV-related service provision [ 61 ], and care engagement [ 62 ]. An umbrella review of 39 systematic reviews of the effectiveness of volunteer workers concluded that they were as good as or better in supporting positive outcomes for a variety of health conditions, however, they were not as good at complex tasks, such as diagnosis and counselling.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, while prior HIV treatment interventions, in particular, have adopted a 1:10 ratio of navigator-peers [ 57 ], this was perceived as unsustainable for a volunteer force. These findings are consistent with concerns among stakeholders across SSA [ 58 ], and in Nigeria more specifically [ 59 ], about efficiencies in systems of HIV care given reduced funding from external donors, which have impacted the quantity [ 60 ] and quality of HIV-related service provision [ 61 ], and care engagement [ 62 ]. An umbrella review of 39 systematic reviews of the effectiveness of volunteer workers concluded that they were as good as or better in supporting positive outcomes for a variety of health conditions, however, they were not as good at complex tasks, such as diagnosis and counselling.…”
Section: Discussionsupporting
confidence: 75%
“…While there has not been extensive research on key stakeholders' perspectives of the sustainability of FP efforts in Nigeria, there has been research into stakeholders' perspectives on the sustainability of HIV/ AIDS services in Nigeria [30][31][32]. Itiola and Agu's 2018 qualitative study on country ownership and sustainability of Nigeria's HIV/AIDS supply chain system was conducted with key stakeholders representing each geopolitical zone of the country to better understand what happens when large donors decrease their levels of funding for key health issues.…”
Section: Discussionmentioning
confidence: 99%
“…With Unification, all the supply chain systems were unified into one by July 2014 12 -see Itiola & Agu, 2018 for a more comprehensive description of the HIV/AIDS Supply Chain System. 13…”
Section: Settingsmentioning
confidence: 99%